The Role of Blockchain Technology in Increasing Economic Transparency and Public Trust - Rijal, Syamsu; Saranani, Fajar (Technology and Society Perspectives (TACIT), 2023)
Blockchain technology has become one of the most promising technological innovations in recent years. The main advantages of blockchain technology are high transparency, security, and data integrity. Therefore, this technology has attracted attention in various sectors, including the economy. This research aims to examine the role of blockchain technology in enhancing economic transparency and public trust. This study is a literature review that adopts a qualitative method, which means it will analyse and interpret data by utilising information and texts derived from various sources. The results of the study show that blockchain technology has proven itself to be a highly effective tool for achieving this goal. In an increasingly connected and data-dependent society, economic transparency and public trust are key factors in sustainable economic growth and social stability.